Behavior management : from theoretical implications to practical applications - Maag, John W., 1956- (San Diego, Calif. : Singular, 1999)
Introduction to behavior management. Impediments to managing behavior. Origins of behavior management. Basic principles of behavior. Functional assessment of behavior problems...
Keywords: Education; Behavior modification; Classroom management -- United States; Problem children -- Education -- United States